Potret Pendidikan dan Kemiskinan di Indonesia dalam Novel Laskar Pelangi Karya Andre Hirata - Rini Widiastuti (Badan Pengembangan dan Pembinaan Bahasa, 2021)
This paper will examine and reflect on the relationship between literature and education, by addressing the issues surrounding the development of the education system in Indonesia through Andrea Hirata's Laskar Pelangi